SANKSI PIDANA DENDA EMAS DAN HUKUMAN CAMBUK DALAM QANUN ACEH - Sopiani (2021)
The birth of the Aceh Qanun regarding the Law of Jinayat which regulates the criminal sanction of gold fines and caning is not based on the formulation and there are problems in the community. Law 12 of 2011 concerning the Establishment of Legislative Regulations states that regional regulations / qanuns are in the form of a maximum imprisonment of 6 months or a maximum fine of Rp.50,000,000.00 and can regulate the threat of imprisonment or fines in accordance with statutory regulations. other invitations. This study aims to deepen and analyze the criminal penalties of gold and caning in the Aceh Qanun. The research method in this research is normative juridical legal research, carried out by examining theories, legal principles, norms, rules of legislation, and others. According to the author of the Aceh Qanun, the regulation of the amount and limits of criminal sanctions must be in accordance with the laws and regulations above.